A DNA Based Biosensor Amplified With ZIF-8/Ionic Liquid Composite for Determination of Mitoxantrone Anticancer Drug: An Experimental/Docking Investigation - Alizadeh, Marzieh; Azar, Parviz Aberoomand; Mozaffari, Sayed Ahmad; Karimi-Maleh, Hassan; Tamaddon, Ali-Mohammad (Frontiers in Chemistry, 2020)
An ultrasensitive DNA electrochemical biosensor based on the carbon paste electrode (CPE) amplified with ZIF-8 and 1-butyl-3-methylimidazolium methanesulfonate (BMIMS) was fabricated in this research. The DNA/BMIMS/ZIF-8/CPE was used for selective determination of mitoxantrone anticancer drug in aqueous solution, resulting in good catalytic effect and a powerful ability for determining mitoxantrone. Also, the interaction of mitoxantrone anticancer drug with guanine bases of ds-DNA was used as a powerful strategy in the suggested biosensor, which was confirmed with docking investigation. Docking study of mitoxantrone into ds-DNA sequence showed the intercalative binding mode of mitoxantrone into the nitrogenous-based pairs of ds-DNA. The effective factors such as ds-DNA concentration, temperature, buffer types, and incubation time were also optimized for the fabricated mitoxantrone biosensor. The results showed that, under optimum condition (T=25 °C; incubation time=12 min; pH= 4.8 acetate buffer solution and [DNA] = 50 mg/L), the DNA/BMIMS/ZIF-8/CPE could be used in mitoxantrone assay in the concentration ranged from 8.0 nM to 110 µM with detection limit of 3.0 nM. In addition, recovery data between 99.18 and 102.08% were obtained for determination of mitoxantrone in the injection samples using DNA/ZIF-8/BMIMF/CPE as powerful biosensors.